A new species of Ornithodoros (Acari: Argasidae), parasite of Microlophus spp. (Reptilia: Tropiduridae) from northern Chile - Venzal, José Manuel (2013)
A new species, Ornithodoros microlophi (Acari: Argasidae), belonging to the subgenus Alectorobius is described from larvae collected on the lizards Microlophus atacamensis (Donoso-Barros, 1966) and Microlophus quadrivittatus (Tschudi, 1845) (Squamata: Tropiduridae) in continental and insular localities from northern Chile. Larvae of O. microlophi can be distinguished from other Neotropical species of the genus Ornithodoros by a combination of the following characters, namely 10 pairs of ventral setae, venter with 6 pairs of sternal setae, dorsal plate pyriform, 19–21 pairs of dorsal setae (typically 20), 13 pairs are dorsolateral and 7 pairs are central, and hypostome with dental formula 4/4 in medial portion and apex pointed. Phylogenetic analysis of 16S rDNA sequences suggests that O. microlophi represents an independent lineage within Neotropical species of the Argasidae.